Band Milestones as Strategy for Mapping Students’ Musical Progress in GJKI Bandung Raya - Piter Sembiring; Clarisa Jesika Korina Tiurmauli Hutapea; Marsel Ridky Maulana; Lee Ji Heon (Universitas Negeri Surabaya, 2025)
This study examines students’ musical development in a church-based band learning environment using a milestone framework to map technical, musical, and collaborative progress. Ten students from GJKI Bandung Raya participated in rehearsals involving instrument-specific training, group coaching, and arrangement work. Data were collected through observation, interviews, and documentation, then analysed using thematic procedures and Miles and Huberman’s analytic stages. Findings indicate that students demonstrated measurable growth in tempo stability, harmonic understanding, dynamic control, cue responsiveness, and role clarity. Collaborative progress was also evident, particularly in rhythmic coordination, structural navigation, and real-time problem solving during rehearsals. Challenges such as mid-song tempo instability, dynamic imbalance, and vocal inaccuracy required adaptive instructional adjustments that supported sustained improvement. The milestone approach proved effective for identifying learning indicators in community-based band settings. The study contributes practical and theoretical insights and suggests future development of structured milestone-based band curricula.